Les bateaux-lavoirs lavallois ou l’exceptionnelle longévité d’une flotte buandière - Sylvie Garnavault (In Situ)
To begin with, there were places called ‘arrivoirs’, places of arrival created along the banks of the river Mayenne at Laval and used principally for washing activities. During the Second Empire, the local authorities undertook the construction of quays in order to protect the city, subject to periodic flooding. This explains the appearance of the first washing boats, designed to give washerwomen, whether professional or not, access to the river. These became a picturesque local feature but were first and foremost places of work and sociability for the ‘poules d’eau’, the ‘moorhens’ who spent their busy working days there. At the end of the nineteenth century, Laval’s ‘laundry fleet’ comprised 23 vessels. In 1969, one of the last two of these vessels still moored at Laval ceased its activities, finally made redundant by the democratisation of the washing machine. This vessel was the Saint-Julien, a flat-bottomed double-decker boat originally built in the Maine-et-Loire department in 1904. The upper deck served as a laundry, but also as a dwelling for the owner and his family. The hull of the vessel was the washing facility itself, its central space occupied by two boilers that heated the water for the tubs placed above. The boat could accommodate up to 40 washerwomen. The Saint-Julien and a neighbouring vessel on the quayside have been acquired by the city of Laval and protected as historic monuments. Both vessels sank in 2009 but were rescued simultaneously and the first has now been restored and returned to its original position where visitors are welcomed aboard. The second washing boat is still awaiting a restoration programme. The Saint-Julien and Saint-Yves are unique in France, the last washing boats to bear witness to a traditional riverside activity which has now disappeared completely.